2013
DOI: 10.1017/s1041610213001336
|View full text |Cite
|
Sign up to set email alerts
|

Substitute consent practices in the face of uncertainty: a survey of Canadian researchers in aging

Abstract: Findings underscore the need to clarify who may authorize an incapacitated adult's participation in research. Meanwhile, people should inform their relatives of their desire to participate or not in research in the event of incapacity, given researchers' tendency to turn to family for consent, even where not supported by law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Uncertainty about how the legislation should be interpreted has also been reported in a survey of care home managers and key informant interviews exploring research in care homes 2425 surveyed Canadian researchers and found that there was a lack of awareness about who can act as proxy decision-maker for research 25. They called for greater clarity and education about who can act as proxy decision-maker 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainty about how the legislation should be interpreted has also been reported in a survey of care home managers and key informant interviews exploring research in care homes 2425 surveyed Canadian researchers and found that there was a lack of awareness about who can act as proxy decision-maker for research 25. They called for greater clarity and education about who can act as proxy decision-maker 25.…”
Section: Discussionmentioning
confidence: 99%
“…Bravo et al 25 surveyed Canadian researchers and found that there was a lack of awareness about who can act as proxy decision-maker for research 25. They called for greater clarity and education about who can act as proxy decision-maker 25. An earlier study led by the same author examined knowledge of the legislation governing proxy consent to both treatment and research of four Canadian groups (older adults, informal caregivers of cognitively impaired individuals, researchers in ageing and members of research ethics boards) 15.…”
Section: Discussionmentioning
confidence: 99%
“…A further argument in support of family members’ involvement in dementia research relates to the above-mentioned evidence that people suffering from AD can retain the capacity to appoint a proxy decision-maker even when they lose the capacity to give consent to research participation [32]. However, one study investigating consent practices of researchers in aging reported the soliciting of consent from family members to include people deemed incapable of consent in research protocols, even in jurisdictions where such authority is uncertain at law [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Due in part to this legal complexity, a lack of knowledge about research involving adults who lack capacity, and paternalistic attitudes generally, may result in gatekeeping practices by researchers and health and social care professionals towards this population [73,74]. Involving health and social care professionals as a consultee or legal representative relies on them having the time and willingness to be involved.…”
Section: The Challengesmentioning
confidence: 99%